Structured commodity finance - Suták, Péter (Applied Studies in Agribusiness and Commerce, 2012)
Over the past years, the financial stock market – providing the capital demand that is the result of stockpiling and the characteristic strong seasonality observed in the agricultural sector – has increasingly grown and become more “used” by market participants. Its size had reached an annual value of 200 billion HUF, of which agricultural products had received the largest proportion through the various market participants (producers, integrators, traders, feed producers, mills). In the meantime, this market had become part of the competition between the commercial banks that are the largest financers of the sector, due to which the financing credit institutions had undertaken increasing risk levels, with respect to both degree of financing and the VAT financing related to stockholding. The practice of commodity financing by banks display a rather varied picture at present. Considering the exceptional degree of fall in prices and the actions of companies totally disregarding business ethics in 2008, it seems necessary to reveal the full scope of risks inherent in commodity financing. The primary aim of such an exercise is to ensure the prudent operation of refinancing activities for commercial banks. The inherent risks in trade financing – as has been proven by the experiences of previous years – are not found primarily in the goods themselves, but rather at the actual storage facility and also emerge in relation to clients, as well as the inadequate and ineffective risk management of price volatility by the financers. Therefore, the establishment of banking risk management and risk prevention techniques, including the development of new financing procedures become indispensable, minimizing all types of risks that had emerged in previous years.